Analisis Pengawasan Fasilitas Bandar Udara oleh Unit Terminal Inspection Service pada PT.Angkasa Pura II Di Bandar Udara Husein Sastranegara Bandung - Gilar Pramudya; Gallis Nawang Ginusti (Institut Nalanda, 2024)
At Bandung's Husein Sastranegara Airport, the Terminal Inspection Service (TIS) Unit is tasked with supervising and ensuring that terminal facilities function optimally in accordance with service standards. This research aims to find out how the monitoring system is carried out by the Terminal Inspection Service (TIS) unit and what obstacles are faced by Terminal Inspection Service (TIS) officers in the process of monitoring facilities at T.Angkasa Pura II at Husein Sastranegara Airport. This research uses qualitative methods with data collection techniques through interviews, observation and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The research was carried out at Husein Sastranegara Airport in Bandung for 1 month, from 1 August to 31 August 2024. The results obtained in the research are monitoring of airport facilities by the Terminal Inspection Service (TIS) Unit at Husein Sastranegara Airport carried out in collaboration with the Airport Authority for more effective monitoring and quick response to emergency situations. Challenges such as technological and environmental limitations can be overcome by procuring advanced technology, increasing coordination, and adjusting regulations. This effort aims to create a safe and comfortable airport, as well as support smooth flight operations.